1994
DOI: 10.1097/00004032-199409000-00008
|View full text |Cite
|
Sign up to set email alerts
|

137Cs Concentration Among Children in Areas Contaminated With Radioactive Fallout from the Chernobyl Accident

Abstract: The level of radiation exposure in children in Belarus caused by the Chernobyl accident was investigated on the basis of whole body 137Cs count. The subjects were 10,062 children (4,762 boys and 5,300 girls) in Mogilev and Gomel, Belarus, who received Chernobyl Sasakawa Health and Medical Cooperation Project health examinations from May 1991 to December 1992 and who were 5-16 y old at the time of examination. The median whole body 137Cs count per body weight varied from 21-48 Bq kg-1 and from 28-126 Bq kg-1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Mean soil-contamination value of 5.17 Ci/km2 in patients' residences is also far higher than the background 137Cs level of 0.094 Ci/km2 in Nagasaki in 1990 (Shimazaki et al, 1992). The median level of whole-body count showed a significant correlation with the median level of soil 137Cs contamination (Hoshi et al, 1994), and soil 137Cs level might reflect the soil-contamination level of short-lived radioisotopes just after the accident. But the annual effective dose equivalent was less than the public dose limit of 1 mSv/y recommended by the International Commission on Radiological Protection in 1990 (Hoshi et al, 1994).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Mean soil-contamination value of 5.17 Ci/km2 in patients' residences is also far higher than the background 137Cs level of 0.094 Ci/km2 in Nagasaki in 1990 (Shimazaki et al, 1992). The median level of whole-body count showed a significant correlation with the median level of soil 137Cs contamination (Hoshi et al, 1994), and soil 137Cs level might reflect the soil-contamination level of short-lived radioisotopes just after the accident. But the annual effective dose equivalent was less than the public dose limit of 1 mSv/y recommended by the International Commission on Radiological Protection in 1990 (Hoshi et al, 1994).…”
Section: Resultsmentioning
confidence: 90%
“…The median level of whole-body count showed a significant correlation with the median level of soil 137Cs contamination (Hoshi et al, 1994), and soil 137Cs level might reflect the soil-contamination level of short-lived radioisotopes just after the accident. But the annual effective dose equivalent was less than the public dose limit of 1 mSv/y recommended by the International Commission on Radiological Protection in 1990 (Hoshi et al, 1994). Although no significant dose-response relationship was confirmed, our study showed that most pediatric cancer cases occurred in the background of low-level radio-contamination.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although some exploratory retrospective work commenced within areas heavily contaminated by fallout from the Chernobyl reactor within five years after the accident (Bailiff, 1997), the work to obtain closer integration of luminescence techniques with the established approaches of dose reconstruction only commenced several years later. In an initiative that formed part of the Chernobyl Sasakawa Health and Medical Foundation Project (Hoshi et al, 1994) a joint JapaneseBelarusian team undertook fieldwork to sample buildings in 14 contaminated settlements Belarus (Sato et al, 2002). Working independently from the effort underway in Belarus, a collaborative group of institutes from the EU states, the Ukraine and Russia undertook fieldwork in three settlements in the Ukraine and Russia (Bailiff et al, 2004a andBailiff et al, 2005).…”
Section: Chernobylmentioning
confidence: 99%